Asymmetric somatic hybridization induces point mutations and indels in wheat. (December 2015) - Wang, Mengcheng; Liu, Chun; Xing, Tian; Wang, Yanxia; Xia, Guangmin
Abstract Background Allopolyploid genome needs wide structural variation to deal with genomic shock. The introgression line, generated via asymmetric somatic hybridization, is introgressed with a minimum of exogenous chromatin, which also leads to genomic shock to induce genetic variation. However, the extent of its genomic variation and its difference from allopolyploidies remains unknown. Methods Here, we explored this issue using the bread wheat cultivar SR3, a derivative of an asymmetric somatic hybrid between the cultivar JN177 and an accession of tall wheatgrass (Thinopyrum elongatum ). The ESTs (expressed sequence taqs) were large-scale sequenced using the cDNA library constructed in each of SR3 and JN177. Point mutations and indels (insertions and deletions) of SR3 were calculated, and their difference from the genetic variation of bread wheat and its ancestors were compared, with aim to analyze the extent and pattern of sequence variation induced by somatic hybridization. Results Both point mutations and indels (insertions and deletions) were frequently induced by somatic hybridization in the coding sequences. While the genomic shock caused by allopolyploidization tends to favor deletion over insertion, there was no evidence for such a preference following asymmetric somatic hybridization. The GC content of sequence adjacent to indel sites was also distinct from what has been observed in allopolyploids. Conclusions This study demonstrates that asymmetric somatic hybridization induces high frequency of genetic variation in a manner partially different from allopolipoidization. Asymmetric somatic hybridization provides appropriate material to comprehensively explore the nature of the genetic variation induced by genomic shock.